(untitled) (Jurnal Teknologi (Sciences & Engineering), 2017)
This paper proposes methods to reduce energy consumption for the transportation of coal slurries. Spiral pipe is one of the methods that can improve drag reduction at certain velocity as well as prevent decomposition at the pipe bottom and generate homogenous particles distribution. The objective is to investigate the influence of using spiral pipe to pressure drop and homogeneity of coal slurries. The pipe angles (Î²) are 140, 230, 400 and 560, the pipe test loop is set up with entrance length 3000 mm. Pressure Transducer and pitot tube are used in the measurements. Percentage of the particle concentrations are varied by weight of 30 %, 40 % and 50 %. The helical angle gives significant effect to eliminate decomposition at the pipe bottom. At CW 50 %, homogeneity of the slurries can reach around 96 % at helical angle 230, It means the mixture between solid material and water more uniform, using circular pipe the homogeneity is only 74 %. Weight concentration of the solid particles and Reynolds number gives significant effect to the drag reduction. Flow of CW =50 % slurry at Re 5x104 through 23Â° spiral pipe can increase drag reduction by about 30%. Velocity profiles were obtained from numerical CFD simulation validated experimental results make clear the flow characteristics.